(untitled) (Clinics, 2016)
OBJECTIVE: To test the hypothesis that intravenous use of methotrexate associated with lipid nanoemulsions can achieve superior anti-inflammatory effects in the joints of rabbits with antigen-induced arthritis compared with commercial methotrexate. METHODS: Arthritis was induced in New Zealand rabbits sensitized with methylated bovine serum albumin and subsequently intra-articularly injected with the antigen. A nanoemulsion of methotrexate labeled with 3H-cholesteryl ether (4 mg/kg methotrexate) was then intravenously injected into four rabbits to determine the plasma decaying curves and the biodistribution of the methotrexate nanoemulsion by radioactive counting. Additionally, the pharmacokinetics of the methotrexate nanoemulsion were determined by high-pressure liquid chromatography. Twenty-four hours after arthritis induction, the animals were allocated into three groups, with intravenous injection with saline solution (n=9), methotrexate nanoemulsion (0.5 µmol/kg methotrexate, n=7), or commercial methotrexate (0.5 µmol/kg, n=4). The rabbits were sacrificed 24 h afterward. Synovial fluid was then collected for protein leakage and cell content analyses and synovial membranes were collected for histopathological analysis. RESULTS: The methotrexate nanoemulsion was taken up mainly by the liver and the uptake by arthritic joints was two-fold greater than that by control joints. The methotrexate nanoemulsion treatment reduced leukocyte influx into the synovial fluid by nearly 65%; in particular, mononuclear and polymorphonuclear cells were reduced by 47 and 72%, respectively. In contrast, cell influx was unaffected following treatment with commercial methotrexate. Protein leakage into the arthritic knees of the rabbits was also more limited following methotrexate nanoemulsion treatment than following commercial methotrexate treatment. CONCLUSIONS: The intravenous methotrexate nanoemulsion showed anti-inflammatory effects on the synovia of arthritic joints that were clearly superior to the effects of a commercial methotrexate preparation. This result is conceivably due to greater methotrexate uptake by the joints when the drug is associated with a nanoemulsion.